FAKTOR PENGHAMBAT PENYEMBUHAN LUKA DI RS MELATI PERBAUNGAN - Mesrida Simarmata; Nurhaida Nurhaida (Jurnal Online Keperawatan Indonesia, 2021)
Diabetes mellitus, a chronic metabolic disorder characterized by high blood sugar levels as a result of insulin insufficiency. This is due to a disruption in the definition of insulin production, the beta cells of the pancreas gland are due to the lack of responsiveness of the body's cells to insulin. Chronic wounds that are difficult to heal due to disruption of wound healing by systemic, local and other factors so that the wound does not heal with normal wound healing time. Chronic wounds occur because primary healing is delayed and repeated over a period of time. This research is a descriptive study, the aim of which is to look at "Factors That Inhibit The Healing Process Of Diabetes Mellitus Wounds At Melati Hospital. Perbaungan 2019, using a total sampling of 30 respondents, obtained results with old wound healing based on the majority age> 45 years as many as 25 people (83.3%), based on the majority gender based on female gender as many as 21 people (70%) The majority of treatment duration was based on length of treatment> 20 weeks as many as 20 people (66.6%), based on the majority of wound stages based on stage III-IV as many as 21 people (70%). Based on the results of the study, it is recommended that health workers provide information about the factors that hinder the healing process of diabetes mellitus wounds